¿Cómo pintar el mural de una mujer-agua? - Álvarez-Mora, Mauricio (2023)
This essay is about the work of Xinia Briceño, a woman of water, who was born in one of the rainiest areas of Costa Rica, in the town of Siquirres. She dedicated her life to fighting against the contamination of water by agrochemicals resulting from the pineapple agribusiness. She died prematurely and was a reference in the defense of the community's right to drinking water, which was contaminated by the chemical bromacil, affecting more than 2,000 people in the area. Xinia and her struggle inspired hundreds of university students who found in her a teacher and a true champion in the defense for the right to water